In vitro dose and duration dependent approaches for the assessment of ameliorative effects of nanoconjugated vancomycin against Staphylococcus aureus infection induced oxidative stress in murine peritoneal macrophages. (February 2016) - Chakraborty, Subhankari Prasad; Pramanik, Panchanan; Roy, Somenath
Abstract: Aims: The present study was aimed to evaluate the in vitro ameliorative effect of nanoconjugated vancomycin (NV) against vancomycin sensitive and resistant strains of Staphylococcus aureus infection-induced oxidative stress in murine peritoneal macrophage. Methods: Peritoneal macrophages from mice were treated with VSSA and VRSA (5 × 10 6 CFU/mL), VSSA + NV (5–250 μg/ml) and VRSA + NV (5–250 μg/ml) for 18 h, having 3 h interval in culture media; and the superoxide anion generation, lipid peroxidation, protein oxidation, antioxidant enzymes status and glutathione enzymes activity were monitored. Results: The significantly increased free radical generation, lipid peroxidation, protein carbonyls and oxidized glutathione levels were observed in VSSA and VRSA treated group as compared to control group; where as reduced glutathione level, antioxidant enzymes status and glutathione dependent enzymes were decreased significantly. All these changes come near to control in NV treated group in a dose and duration dependent fashion. Among the different doses and duration intervals of NV, maximum ameliorative effect was observed by 100 μg/ml for 12 h treatment which does not produce any damage to the cell. Conclusions: These findings suggest the potential use and beneficial role of nanoconjugated vancomycin as a modulator of S. aureus infection-induced cellular damage in murine peritoneal macrophage. Graphical abstract: Highlights: Infection of vancomycin sensitive and resistant strain of Staphylococcus aureus in murine peritoneal macrophage. S. aureus infection-induced oxidative stress in murine peritoneal macrophages. In vitro ameliorative role of nanoconjugated vancomycin (NV) against S. aureus infection-induced oxidative stress in murine peritoneal macrophages.